Perencanaan dan Pengendalian Produksi Grey Cloth Dengan Metode Capacity Requirement Planning - Hartono, Arif (Jurnal Teknik Industri, 2007)
PT "X" on the weaving department had oven the material accumulation was caused by buying material is over. Another always have under capacity work time result cut back schedule material shipping. So that needs arrangement adjustment from fist capacity and needs. And than recalculation, amount ordering material in order to not happened material accumulation. MRP method use for determine exact lot sizing. The comprise amount ordering and frequency ordering. Compare the suggestion cost before suggestion lot sizing occur fist lot sizing, so can determine lot sizing method use balanced between load and capacity. Add load and capacity or decrease load and capacity. From comparison fist capacity and suggestion capacity so can a profit capacity. Based on the analysis we can know on the suggestion lot sizing have efficiency 78.26% concerning fist lot sizing. The suggestion capacity experience decrease 17.14% from fist capacity. And than efficiency labor force cost 13.55% occur fist labor force cost.